2018
DOI: 10.56093/ijas.v88i12.85449
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and effect of decontamination processes on reduction of cypermethrin in okra (Abelmoschus esculentus) fruits

Abstract: Persistence of cypermethrin and decontamination processes on reduction of cypermethrin residues was studied in okra (Abelmoschus esculentus L.) fruits following foliar application of formulation at dose of 50 and 100 g a. i./ha in a field at the Research field of CCS HAU, Hisar, India. Samples of okra fruits were collected periodically and residues were estimated by GC-ECD and confirmed by GC-MS. The average initial deposits of cypermethrin were 0.119 and 0.272 mg/kg in the okra fruits at single and double dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…An experiment was carried out by Chauhan and Bajapai [55], and the findings showed that plants given 10.0 mg Zn produced the maximum number of fruits per plant, as well as the highest number of seeds per fruit, the highest weight of fresh fruit, and the highest weight of seeds. According to Sharma et al, [56], the application of 7.5 kg of zinc per hectare to the soil significantly increased the plant height, the number of branches per plant, the leaf area, the chlorophyll content, the fruit length, the number of fruits per plant, the fruit yield per plant, per hectare, as well as the protein and crude fiber content in fruits.…”
Section: Okramentioning
confidence: 99%
“…An experiment was carried out by Chauhan and Bajapai [55], and the findings showed that plants given 10.0 mg Zn produced the maximum number of fruits per plant, as well as the highest number of seeds per fruit, the highest weight of fresh fruit, and the highest weight of seeds. According to Sharma et al, [56], the application of 7.5 kg of zinc per hectare to the soil significantly increased the plant height, the number of branches per plant, the leaf area, the chlorophyll content, the fruit length, the number of fruits per plant, the fruit yield per plant, per hectare, as well as the protein and crude fiber content in fruits.…”
Section: Okramentioning
confidence: 99%